Pengaruh Digital Marketing dan Product Innovation Terhadap Marketing Performance dengan Competitive Advantage sebagai Variabel Mediasi (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of digital marketing and product innovation on the marketing performance of culinary SMEs in Semarang City, with competitive advantage as a mediating variable. Digital marketing is considered effective in expanding market reach, building consumer interactivity, and trust. Product innovation plays a crucial role in creating differentiation and unique value, thereby strengthening the competitive position of SMEs. The research employs a quantitative method with a survey approach and data collection through questionnaires distributed to 100 culinary SME actors in Semarang City. Data analysis was conducted using multiple regression models and mediation tests. The results indicate that digital marketing and product innovation have a significant positive effect on competitive advantage. However, the direct impact of digital marketing, product innovation, and competitive advantage on marketing performance was not significant. Competitive advantage acts as a mediating variable linking these factors to marketing performance. These findings underscore the importance of building competitive advantage through effective digital marketing strategies and market-responsive product innovation to enhance sustainable marketing performance. The practical implications of this study recommend SMEs optimize the use of digital marketing and product innovation to strengthen competitiveness and business growth